Assessment of an aqueous seed extract of Parkia clappertoniana on reproductive performance and toxicity in rodents. (5th June 2016) - Boye, Alex; Boampong, Victor Addai; Takyi, Nutifafa; Martey, Orleans
Abstract: Ethnopharmacological relevance: The seeds of Parkia clappertoniana Keay (Family: Fabaceae) are extensively used in food in the form of a local condiment called 'Dawadawa' in Ghana and consumed by all class of people including sensitive groups such as pregnant women and children. Also, crudely pounded preparations of P. clappertoniana seeds are used as labor inducing agent in farm animals by local farmers across northern Ghana where nomadism is the livelihood of most indigenes. Ecologically, P. clappertoniana is extensively distributed across the savannah ecological zone of many African countries where just like Ghana it enjoys ethnobotanical usage. Although, many studies have investigated some aspects of the pharmacological activity of P. clappertoniana, none of these studies focused on the reproductive system, particularly its effects on reproductive performance and toxicity. To contribute, this study assessed the effect of aqueous seed extract of P. clappertoniana (PCE) on reproductive performance and toxicity in Sprague-Dawley rats and ICR mice.Methods: After preparation of PCE, it was then tested on rodents at different gestational and developmental windows (1-7, 8-14, and 15-term gestational days) to assess the following: mating behavior, implantation rate, maternal and developmental toxicities. Generally, animals were randomly grouped into five and treated as follows: normal saline group (5 ml/kg po ), cytotec (misoprostol) group (200 mg/kg po ), folic acid group (5 mg/kg po ), and PCE groups (100, 200, and 500 mg/kg po ), however, these groupings were varied to suit the specific requirements of some parameters. For acute toxicity, animals were orally administered PCE (3 and 5 g/kg for mice and rats respectively).Results: PCE-treated rats showed improved mating behavior compared to control rats. PCE improved implantation rate compared to misoprostol-treated rats. On the average, PCE-treated rats delivered termed live pubs at 21 days compared to that of folic acid-treated rats at 23 days. Also, PCE-treated rats showed no observable maternal and developmental toxicities compared to folic acid and control rats. PCE (3–5 g/kg po ) was orally tolerated in rodents.Conclusion: Oral administration of Parkia clappertoniana seed extract improves reproductive performance in rodents with no observable maternal and developmental toxicity. Graphical abstract: